The Influence of Probing-Prompting Learning Model Towards Reading Comprehension of English Students at the Eleventh Grade of Senior High School No. 1 Jambi City - Ahmad Fajri; Yanti Ismiyati; Siti Aisyah (Universitas Batanghari Jambi, 2022)
This research aims to find out whether there is any influence of probing-prompting learning model towards reading comprehension of English students at the eleventh grade of Senior High School No. 1 Jambi City. This type of research is a quasi-experimental with a total population of 347 people. Through simple random sampling technique, 34 students of Class XI IPS 2 were selected as the control class and 36 students of Class XI IPS 3 were selected as the experimental class. The technique of collecting data is by distributing questions to research respondents. In this research, the data analysis technique was using the t test on the Statistical Package for the Social Sciences (SPSS) for Windows version 25 program. The results of this research indicate that (1) students’ reading comprehension in English subject taught using the probing-prompting learning model obtained an arithmetic mean of 75.89; (2) students’ reading comprehension in English subject taught using the lecture-based learning model obtained an arithmetic mean of 69.24; and (3) students’ reading comprehension in English subject taught using the probing-prompting learning model are higher than students’ reading comprehension in English subject taught using lecture-based learning model with a value of Sig. 0.000 > 0.05. Furthermore, there is an influence on the use of the probing- prompting learning model towards students’ reading comprehension as evidenced by the increase in students’ learning outcomes.Keywords: Probing-Prompting Learning Model, Reading Comprehension